Transfer of property and private international law - Carruthers, Janeen M. (Cheltenham, UK : Edward Elgar Publishing Limited, 2016)
"[This book brings together] articles on the subject of transfer of property and private international law, ranging from the early twentieth century to present day. The first volume focuses on classic principles concerning the lex situs rule, as well as on specialities regarding immovable property, tangible movable property and intangible property, conditional sale and securities transactions, goods in transit and confiscation of property. The second volume is devoted to an in-depth and insightful discussion of cultural property and private international law. Together with an original introduction by the editor, this collection provides ... 65 articles, dating from 1919 to 2015"--
Volume I. Introduction / Janeen M. Carruthers -- Part I: Lex situs rule : classic principles -- Part II: Specialties regarding immovable property and tangible movable property -- Part III: Specialties regarding intangible property -- Part IV: Conditional sale, security and goods in transit -- Part V: Confiscation, expropriation and nationalization -- Volume II. Part I: Cultural property.
Includes bibliographical references and index.
Keywords: Transfer (Law); Conflict of laws; Conflict of laws; Transfer (Law)